The geology and ore deposits of the Quiruvilca district, Peru - Lewis, Richard W. (1956)
The Quiruvilca copper-lead-zinc district is in the Department of La Libertad in north-central Peru. The only large mine in this area is the Quiruvilca mine, owned and operated by the Northern Peru Mining and Smelting Co. The mine lies in bedded andesitic and basaltic volcanics, which have been intruded by a small plug of andesite. Numerous dikes and breccia pipes cut rocks surrounding the small plug. To the west of the Quiruvilca mine are four dacite plugs enclosed by sandstone, and 7 kilometers to the east slightly metamorphosed Cretaceous sediments crop out. The ore deposits of the district are mesothermal and epithermal and were formed by fissure filling. Mineralization followed a pre-existing set of tension and shear fractures and the veins form a well-defined oblique grid pattern. Only a few of the many veins in the area are productive. The wider ones, which average a meter in width, are being exploited. On the basis of mineralogy, the mineralized area can be divided into four distinct zones. From the center outward these zones are: 1) the Enargite zone, 2) the Transition zone, 3) the Lead-Zinc zone, and 4) the Stibnite zone.